2009
DOI: 10.1007/s11013-009-9138-2
|View full text |Cite
|
Sign up to set email alerts
|

Metal Music and Mental Health in France

Abstract: Although numerous authors have associated metal music with social problems such as suicide, self-destruction and Satanism, few studies have been undertaken to examine the mental health of fans of heavy metal music. This study attempts to determine if there is a link between mental health and the enjoyment of this type of music in France. The researchers surveyed 333 fans of metal music. Their mental health was evaluated by the Hospital Anxiety and Depression Scale (HADS), a widely used instrument that measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Yet, individual differences in preference may also play a role. For example, a French study on metal music found that fans of this loud and obnoxious type of tune exhibited low levels of both anxiety and depression (Recours, Aussaguel, & Trujillo, 2009). Furthermore, a study on postpartum women demonstrated that some individuals did not experience lower anxiety when obliged to listen to preselected music when at home during a regulated time period (Tseng, Chen, & Lee, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, individual differences in preference may also play a role. For example, a French study on metal music found that fans of this loud and obnoxious type of tune exhibited low levels of both anxiety and depression (Recours, Aussaguel, & Trujillo, 2009). Furthermore, a study on postpartum women demonstrated that some individuals did not experience lower anxiety when obliged to listen to preselected music when at home during a regulated time period (Tseng, Chen, & Lee, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study indicated that the greater the suicidal tendencies of a viewer of a suicide film were, the more he or she tended to use the film for ideas about how to go through life and deal with the own problems (Till, Vitouch, Herberth, Sonneck, & Niederkrotenthaler, 2013). However, despite the vast amount of time people spend on listening to music-the average American spends more than 2.5 hours per day listening to music (see Rentfrow, Goldberg, & Zilca, 2011), and 80% of respondents of a study in Austria indicated that they listened to music on a daily or weekly basis (Huber, 2010)-research on the link between music and suicidality is relatively scarce (Stack, Lester, & Rosenberg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies also showed that heavy metal preference was related to depressive symptoms (15,16) while a recent study from France did not demonstrate such a finding (17). Future studies comparing frequent patrons of heavy metal bars with non-patrons are needed to understand whether being a bar patron has any specific effects on depression risk amongst this population.…”
Section: Discussionmentioning
confidence: 93%